Marine Heterotrophic Bacterial Chemotaxis to Phage-Infected Synechococcus - Moon, Jonathan (Wake Forest University, 2023)
Synechococcus are an important genus of marine cyanobacteria that are estimated to be responsible for approximately one-fifth of oceanic net primary production. Cyanophages are viruses that infect Synechococcus and can alter host gene expression and metabolite exudation prior to and following phage-induced cell lysis. Heterotrophic microorganisms can detect and navigate towards exuded metabolites, which can serve as nutrient sources, through chemotaxis. Thus, marine viruses potentially manipulate microbial interactions with infected hosts which has implications on nutrient exchange and carbon flux. Despite their high abundance and estimated impact on microbial populations, mechanisms of viral influence on the marine ecosystem are not well characterized. Additionally, no published studies have quantified bacterial chemotaxis in response to cyanophage-infected Synechococcus or their exudates. In this study, we utilized microfluidics and video microscopy to investigate the chemotactic responses of the marine heterotrophic chemotactic bacterium Pseudoalteromonas haloplanktis to Synechococcus exudates collected from phage-infected cultures. We also investigated chemotaxis of another marine bacterium, Vibrio alginolyticus, to intact phage-infected Synechococcus. These data build on previous work and provide new evidence to suggest that cyanophages may indeed influence microbial interactions which has the potential to impact our understanding of factors affecting nutrient and carbon flux in the marine environment.